Impact of government interventions on the stock market during Covid-19: A case study in Vietnam - Nguyen, Hong Thang; Huynh, Cong Hoa; Dang, Hoang Minh Quan; Huynh, Thi Thuy Huyen; Pham, Minh Truong; La, Hoang Lam (Journal of Finance - Marketing Research, 2024)
The study aims to analyze the reaction of the stock market to the events of government intervention during the Covid-19 pandemic. The author used data from 341 companies listed on the Ho Chi Minh City Stock Exchange, which were divided into 10 sector groups in the period 2019–2021. Using the event research method, the author analyzed the change in stock market returns around the event date. The research brought many interesting results. Firstly, policy distancing, blockdown, restricting exposure, and restricting travel have a negative effect on the stock market. Secondly, the three times the state bank has reduced interest rates, it shows a positive reaction in the stock market. The findings help investors, regulators, and governments understand the short-term impact of interventions.